A rare case of small cell neuroendocrine carcinoma-lung in pregnancy - Sumathi, N.; Divya, V.; Karthikeyan, Rekha; Begum, Shameema; Sivakumar, Vishnupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Neuroendocrine tumours constitute heterogenous group of cancers that arise from cells in our body which have neuroendocrine cells-mostly from gastro intestinal tract and lungs. They are further divided into low grade, high grade and poorly differentiated ones. It is rare in pregnancy and it poses diagnostic challenge even among experts in the speciality. So, multi-disciplinary approach to management of neuroendocrine carcinomas (NECs) is the key for optimal management.